Sketching interiors : from traditional to digital - Ding, Suining (New York, N.Y. : Fairchild Books)
Getting started -- Perception of edges -- Perception of spaces -- Perception of light and shadow -- Perception of spatial relationships -- Texture -- Presenting materials with markers -- Interior rendering with markers -- Freehand sketching for presentations -- Transforming hand drawings to digital drawings